Landmines and Spatial Development - Chiovelli, Giorgio; Michalopoulos, Stelios; Papaioannou, Elias (Econometrica, 2025)
Landmines affect the lives of millions in many conflict‐ridden communities long after the end of hostilities. However, there is little research on the role of demining. We examine the economic consequences of landmine removal in Mozambique, the only country to transition from heavily contaminated in 1992 to mine‐free in 2015. First, we present the self‐assembled georeferenced catalog of areas suspected of contamination, along with a detailed record of demining operations. Second, the event‐study analysis reveals a robust association between demining activities and subsequent local economic performance, reflected in luminosity. Economic activity does not pick up in the years leading up to clearance, nor does it increase when operators investigate areas mistakenly marked as contaminated in prior surveys. Third, recognizing that landmine removal reshapes transportation access, we use a market‐access approach to explore direct and indirect effects. To advance on identification, we isolate changes in market access caused by removing landmines in previously considered safe areas, far from earlier nationwide surveys. Fourth, policy simulations reveal the substantial economywide dividends of clearance, but only when factoring in market‐access effects, which dwarf direct productivity links. Additionally, policy counterfactuals uncover significant aggregate costs when demining does not prioritize the unblocking of transportation routes. These results offer insights into the design of demining programs in Ukraine and elsewhere, highlighting the need for centralized coordination and prioritization of areas facilitating commerce.